Exploring the predictor of innovative teaching using the job demands-resources model - M. A. Rafsanjani; L. Hakim; N. Laily; P. A. Wijaya; M. R. Irwansyah (Russian State Vocational Pedagogical University, 2021)
Introduction. To keep in pace and remain competitive in today's environment, the lecturer must do innovation in educational process. However, encouraging lecturers' willingness to do innovative teaching is challenging in higher education due to the dual roles as teachers and researchers, which makes the excessive workload and leads to the teacher-researcher role conflict (TRC). Therefore, it is crucial to analyse the impact of TRC on the innovative teaching of lecturers. The present study utilises the job demands-resources (JDR) model due to its high popularity but rarely used in higher education.Aim. This study is aimed to explore the predictor of innovative teaching by utilising the JDR model as a theoretical anchor.Methodology and research methods. This study uses structural equation modelling (SEM) to examine the research model on a random sample of 233 respondents.Results. The results indicated that teacher-researcher role conflict negatively predicted the innovative teaching of the lecturer. Besides, the occupational well-being is a mediating variable to explain the influence of teacher-researcher role conflict on innovative teaching.Scientific novelty. This study reveals innovative teaching predictors in higher education by using the JDR model as a theoretical anchor. The authors found out that teacher-researcher role conflict (TRC) was significantly related to innovative teaching. The high-level expression of TRC will reduce the lecturer's innovative behaviour on teaching activity, and vice versa.Practical significance. The current study provides critical insight into the related stakeholders, such as the universities and related ministries, regarding the negative predictor of innovative teaching. They should discover approaches to reduce the negative effect of TRC on the innovation behaviour of lecturer teaching activity and to address the problem of job role conflict.